Principles of intelligent rail transit - Zhang, Xiubin; Khan, Muhammad Mansoor, 1966-; Halimu, Yeerjiang, 1974- (Advances in high-speed rail technology, 2023)
This book systematically expounds on the scientific principles and technologies of Rail Transit Intelligent Technology based on the high development of artificial intelligence theory and technology. The contents include technical principles, theoretical algorithms and practical engineering technologies of intelligent monitoring of rail transit system, intelligent sensing and identification of train power system, intelligent technology in rail transit system operation, intelligent maintenance of carriage environment, etc.It can be used as a textbook or teaching reference book for related fields in universities, including rail transit system, communication, automation, intelligent equipment design and manufacturing, artificial intelligence, computer science and technology, electrical engineering and automation, etc. It is used as an academic reference for professionals in rail transit system design, operation, and maintenance